Social Ecological Model of Problem Gambling: A Cross-National Survey Study of Young People in the United States, South Korea, Spain, and Finland - Oksanen Atte; Sirola Anu; Savolainen Iina; Koivula Aki; Kaakinen Markus; Vuorinen Ilkka; Zych Izabela; Paek Hye-Jin (MDPI, 2022)
Problem gambling among young people is an emerging trend globally. The online environment in particular offers various possibilities for gambling engagement. This is the first cross-national survey study using the social ecological model to analyze problem gambling, especially in the online context. The study aimed to analyze how different social ecological spheres explain problem gambling. Participants were young people aged 15–25 in the United States (n = 1212), South Korea (n = 1192), Spain (n = 1212), and Finland (n = 1200). The South Oaks Gambling Screen (SOGS) instrument measured problem gambling. The regression models analyzed problem gambling with measures of intrapersonal, interpersonal, organizational, and societal spheres. Spanish participants had the highest SOGS score for problem gambling. In all countries, the variations in problem gambling were best explained by the organizational sphere measures (26%) when compared to the intrapersonal (11%), interpersonal (5%), and societal (3%) spheres. In the full model, the organizational sphere measures had strong associations with problem gambling. These included consumer debt, online gambling community participation, online casino participation, and exposure to online pop-up advertisements. Problem gambling was also associated with conformity to group norms in the interpersonal sphere, and male gender and impulsivity in the intrapersonal sphere. Cross-national results were similar in different countries. Within the final model, gambling community participation had the strongest association with problem gambling (β = 0.23, p < 0.001). The online context plays a major role in problem gambling behavior. The social ecological model is a useful tool for tackling problem gambling and developing preventative measures.